Penerapan Metode Weighted Product Untuk Sistem Pendukung Keputusan Penerima Beasiswa Politeknik Harapan Bersama Tegal - Dyah Apriliani; Slamet Wiyono; Septian Mahardhika (Politeknik Harapan Bersama, 2018)
The scholarship is an educational aid that given to the student in a university. Scholarship are usually given to students, neither economically underprivileged students nor students who have great achievement in an academic field or non-academic field. Politeknik Harapan Bersama as one of education provider in higher education gives scholarships to their students. Scholarship that given to underprivileged students known as Student Learning Aid scholarship (BBM) and scholarships are given to students with academic achievement know as Potential Academic Improvement Scholarship (PPA). The aim of this research is to build decision support system of scholarship recipient using Weighted Product (WP) method. Decision-making system of scholarship receiver is still done by manual, so it takes long time in deciding scholarship receiver. The scholarship grantee decision support system using the Weight Product method is expected to select scholarship receiver automatically when the value for each criterion has been inputted in the system, so resulting in a ranking which calculated using Weight Product method. With this system, the decision making is more objective. The result of this system is the ranking of scholarship receiver candidate.